Colonization of maize seeds by two species of Stenocarpella transformed with fluorescent proteins and assessed through scanning electron microscopy - Carolina da Silva Siqueira; José da Cruz Machado; Carla Lima Corrêa; Ellen Noly Barrocas (Journal of Seed Science)
Stenocarpella maydis and Stenocarpella macrospora species causing leaf spots and stem and ear rots, can be transported and disseminated between cultivating areas through seeds. The objective was to transform isolates of species of Stenocarpella with GFP and DsRed and to correlate different inoculum potentials with the effect caused by the presence of these pathogens in the tissues of maize seeds. The isolates were transformed with introduction of the genes in their nuclei, employing the technique of protoplast transformation. Seeds were inoculated by osmotic conditioning method with transformed and not transformed isolates, with different periods of exposition of seeds to those isolates, characterizing the inoculum potentials, P1 (24 h), P2 (48 h), P3 (72 h) and P4 (96 h). The seeds inoculated with isolates expressing GFP and DsRed in both species elucidated by means of the intensities of the emitted fluorescence, the ability of those organisms to cause infection and colonization in different inoculum potentials. The potentials P3 and P4 caused the highest levels of emitted fluorescence for the colonization by both pathogens. A comprehensive and abundant mycelial growth in the colonized seed structures were well visualized at potential P3 and P4 by means of SEM.